Describing Inequalities in Access to Employment and the Associated Geography of Wellbeing. (February 2014) - Gibb, Kenneth; Osland, Liv; Pryce, Gwilym
This paper addresses three questions. How unequal is access to urban employment and the wellbeing associated with it? What is the monetary value consumers place on access? How does the inequality of access correspond to the geographical pattern of unemployment? A novel approach is developed using the Osland and Pryce house price model to estimate the monetary value of access welfare (MVAW)—the wellbeing associated with living a given distance from employment, taking into account the negative externalities associated with centres of employment and the complexities that arise from the existence of multiple employment centres of varying size. It is found that: MVAW is considerably more unequal than house prices or income; MVAW contributes around 13 per cent of the average value of a house; and the spatial pattern of unemployment rates is highly inelastic with respect to both MVAW and employment, suggesting no evidence of a spatial mismatch.